Frecuencias de corte y niveles de fertilización nitrogenada en rendimiento y calidad del forrraje de morera (Morus sp.), en Cuyuta, Guatemala - Rodríguez, Carlos; Quiñones, Juan A.; Arias, Rodrigo (Agronomía Mesoamericana, 2016)
The trial was conducted at the Centro de Producción Agrícola of ICfA in Cuyuta, Escuintla-Guatemala in order to generate information on the yield and quality of edible mulberry (Morus sp.) roughage treatments consisted of three harvest frequencies (6; 9 and 12 weeks and three fertilization levels of nitrogen (0.40 and 80 kg/ha). A complete randomized block experimental design, with a factorial arrangement (3x3) was used. The cutting height was 0.3 m above the ground level with two sequencies: from August 2nd to September 13 th and from September 13th to December 6th, 1990. In both cases, the 12 week frequency cutting and 80 kg of N were superior to the others (P<=0.01), yielding 6.87 and 6.15 t/ha of dry matter respectively. The yields at 9 weeks were statistically higher than those at 6 weeks. The highest protein percentage of the whole plant, leaves and stalks were produced at 6 weeks. The dry matter digestibility values in vitro showed little variability among treatments, with averages for whole plants, leaves and stalks of 65, 91 and 41 %, respectively. The preceeding data suggests that the mulberry has an excellent potential as a balanced supplement (protein and energy) for dual purpose cattle on the Southern coast of Guatemala.